Decades performance of marine science and education by region and discipline in China - Hua, Tianran; Ruan, Xiao; Qu, Ziyu; Xue, Cheng; Yang, Shengyun; Yao, Yanming; Ye, Guanqiong (Frontiers in Marine Science, 2023)
Strengthening scientific research, technological capacity and sustainable use of oceans in developing countries are the goals of the UN's 2030 Agenda for Sustainable Development. Marine science and education as the key foundation for achieving these goals has been seldom evaluated quantitatively and collectively. This paper adopted the DEA modelling from economics for analyzing the long-term input and output performance of marine science and education at a national scale in China both by region and discipline. It is found that China's marine science and education level has been improving annually in the last decade. The input/output efficiency of science and education in 11 coastal provinces however has slightly declined except Guangdong. The input/output performance among 14 research disciplines was further evaluated and was found the similar improving trends. The input/output efficiency of 70% research disciplines showed an increasing trend while 30% of which showed a slightly declining trend. The results could provide important references for prioritizing the science and education resources allocation both in different coastal regions and marine research disciplines to save the investment and achieve more progress.